THE REALIZATION OF DISAGREEMENT STRATEGIES BY NON NATIVE SPEAKERS OF ENGLISH - Sofwan, Ahmad; Suwignyo, Eko (Language Circle: Journal of Language and Literature, 2011)
This study is meant to investigate the realization of disagreement strategies by non-nativespeakers of English by eliciting data through DCT and role plays from two groups of students:first year students and third year students of English Department. The DCTs and role playscontain 24 situations which are designed in different issues and social status. The resultshowed that most students realized disagreement through contradiction, counterclaim,irrelevancy claim, contradiction and counterclaim, and challenges related to personalinvolvement and non-personal involvement issues in different social status. The contradictionstrategy was dominantly used by the students. Some students realized disagreement throughthe combination of counterclaim and challenge strategy in equal and high-low status related topersonal involvement, and equal and low-high status related to non-personal involvement. Inthis case, students did not only disagree by producing counterclaim response but alsochallenged the previous speaker to provide more evidence related to his/her statement. Thefindings also showed that there is no pragmatic development from first year students to thirdyear students because they produced disagreement strategy in the same way although theyhad different English proficiency level.